ANODIZING-ELECTRODEPOSITION HYBRID COATING BY USING ELECTROLITE SOLUTION AND ZIRCONIUM OXIDE ON THE SURFACE MAGNESIUM AZ31B - Erryani, Aprilia; Elvira, Bunga Rani; Nurbaiti, Syifa Ranggoyani; Syahiddah, Amalia; Mujahidah, Hafsah; Thaha, Yudi Nugraha; Budi, Esmar (National Research and Innovation Agency (BRIN), 2022)
In this study, sodium silicate was synthesized and the characterization of zirconia which was used as a suspension solution for the anodization and electrodeposition processes. The results of the synthesis using FTIR showed the success of making Na2SiO3 with the appearance of absorption from functional groups such as: silanol (Si-OH) and siloxane (Si-O-Si) groups. From the SEM data, it is known that each batch contains elements of oxygen, sodium and silicon, this indicates that Na2SiO3 was successfully synthesized without any detectable impurities. Calcination results using SEM showed that each batch was dominated by zircon elements, but the highest zircon content in batch 3 was 88.81%. XRD data shows that ZrO2 (Monoclinic) dominates, in batch 1 and batch 3 there is Cl2 from ZrOCl. Therefore, the ZrO2 used without the calcination process is in batch 3. Anodizing and Electrodeposition processes are carried out in 3 ways, namely: a. Anodizing, b. Two steps (Anodizing-Electrodeposition, c. One step hybrid (Anodizing and Electrodeposition) with the addition of Al2O3 and Na2O7SiO3 elements to the electrolyte. The surface of magnesium after being coated looks pale white line. SEM data shows that all three methods are coated and contain elements of O, Na, Mg, Zr, Si, K, and in method c. Al is found. The three samples also showed that the sanding process was not optimal and the Zr particles were not evenly distributed on the surface.